Cultivation and Uses of Moringa oleifera as Non-Conventional Feed Stuff in Livestock Production: A Review - Khalid Abdoun; Ahmed Alsagan; Osman Altahir; Gamaleldin Suliman; Ahmed Al-Haidary; Mohammed Alsaiady (Life, 2022)
M. oleifera is the best known and the most utilized of the 14 known species of the genus Moringa. Moringa is used as animal fodder and a medicinal plant as well as in the purification of water. Studies have shown that the day/night temperature of 30/20 °C is the most favorable for M. oleifera germination, plant growth and development. M. oleifera plants prefer sandy, well-drained loam soils due to their susceptibility to waterlogged soil conditions. It is recommended to use fertilizers to improve plant growth and the amount of forage production in areas with low rainfall and extreme temperatures. For forage production, an area of 20 × 20 cm is adapted to 16,000 plants per hectare. Chemical analyses confirmed the presence of different groups of pharmacologically active chemical compounds, as well as functional compounds of nutritional value such as carbohydrates, proteins, fats and vitamins, in M. oleifera. The reviewed literature particularly encourages the use of M. oleifera whole plants as nonconventional forage in ruminants’ nutrition, as well as using M. oleifera leaves or leaves extract as a protein source for broilers and laying hens. M. oleifera in livestock feed with the ultimate goal of producing functional food (meat, eggs and milk) with appropriate contents of human health-promoting substances such as omega-3 and organic selenium remains to be elucidated. Furthermore, M. oleifera inclusion in livestock feed has the potential to increase the shelf-life of animal products during storage and processing. Further research is needed to determine the appropriate supplementation level of different plant parts or their extracts, as well as the appropriate processing methods or treatments of M. oleifera, in order to improve its palatability and consequently enhance the production performance of livestock without compromising animal health.